Social factors affecting the Kazakhstan companies and their innovative optimality. (Journal of Economic Research & Business Administration, 2015)
During the implementation of innovative projects in a paper presented by various factors affecting the company's activities. Innovation is always a way to enhance well-being. Creating new businesses is to find new sources of funding for tribal entrepreneurs. But many entrepreneurs in the internal and external environmental factors do not provide the full cost. Nevertheless, in the direction of social engineeringinnovative trawl system. Consumer demand for the company economic.Increased power production units that provide servicesdirection can be.